Metode Sadd Al-Dzarī’ah dalam Rangka Penangguhan Pernikahan Menghadapi Kehamilan di Luar Nikah - Ningtias, Shavira Ayu; Azka Ahyu , Ifada; Maulana, M. Irfan (Maqasid: Jurnal Studi Hukum Islam, 2025)
This research aims to examine the impact of marriage suspension on pregnant women in the context of the Sadd Al-Dzarī'ah Method. The main objective of this research is to understand the effectiveness of the Sadd Al-Dzarī'ah Method in preventing immoral acts and facilitating the moral rehabilitation process of individuals. This research method uses a qualitative approach by analyzing Islamic legal literature, the fatwas of scholars, and conducting indepth interviews with individuals who have experienced marriage suspension. The results show that the Sadd AlDzarī'ah method has a positive impact by providing opportunities for reflection and self-improvement for individuals involved in relationships outside of marriage. Families play a key role in supporting the rehabilitation process, creating an environment that supports positive change. However, there are also concerns regarding social stigmatization and legal uncertainty that can arise from the implementation of the Sadd Al-Dzarī'ah Method. The conclusion of this study is that the Sadd Al-Dzarī'ah Method has advantages in preventing immorality and fostering individual morals, but also needs more attention regarding its social and legal impacts. Further development can focus on a holistic approach and community education to strengthen collective understanding of the Sadd Al-Dzarī'ah Method.